Current ozone levels threaten gross primary production and yield of Mediterranean annual pastures and nitrogen modulates the response - Calvete-Sogo, Héctor; Elvira, Susana; Sanz, Javier; González-Fernández, Ignacio; García-Gómez, Héctor; Sánchez-Martín, Laura; Alonso, Rocío; Bermejo-Bermejo, Victoria (Atmospheric Environment, 2014)
Pastures are among the most important ecosystems in Europe considering their biodiversity and distribution area. However, their response to increasing tropospheric ozone (O3) and nitrogen (N) deposition, two of the main drivers of global change, is still uncertain. A new Open-Top Chamber (OTC) experiment was performed in central Spain, aiming to study annual pasture response to O3 and N in close to natural growing conditions. A mixture of six species of three representative families was sowed in the field. Plants were exposed for 40 days to four O3 treatments: filtered air, non-filtered air (NFA) reproducing ambient levels and NFA supplemented with 20 and 40 nl l-1 O3. Three N treatments were considered to reach the N integrated doses of “background”, +20 or +40 Kg N ha-1. Ozone significantly reduced green and total aboveground biomass (maximum reduction 25%) and increased the senescent biomass (maximum increase 40%). Accordingly, O3 decreased community Gross Primary Production due to both a global reduction of ecosystem CO2 exchange and an increase of ecosystem respiration. Nitrogen could partially counterbalance O3 effects on aboveground biomass when the levels of O3 were moderate, but at the same time O3 exposure reduced the fertilization effect of higher N availability. Therefore, O3 must be considered as a stress factor for annual pastures in the Mediterranean areas.
Keywords: annual grasslands interactions; Critical levels; Dehesa; Global change; nitrogen; tropospheric ozone

Decreased rates of terpene emissions in Ornithopus compressus L. and Trifolium striatum L. by ozone exposure and nitrogen fertilization. - Llusia, Joan; Bermejo-Bermejo, Victoria; Calvete-Sogo, Héctor; Penuelas, Josep (Environmental pollution (Barking, Essex : 1987), 2014)
Increasing tropospheric ozone (O3) and nitrogen soil availability (N) are two of the main drivers of global change. They both may affect gas exchange, including plant emission of volatiles such as terpenes. We conducted an experiment using open-top chambers to analyze these possible effects on two leguminous species of Mediterranean pastures that are known to have different O3 sensitivity, Ornithopus compressus and Trifolium striatum. O3 exposure and N fertilization did not affect the photosynthetic rates of O. compressus and T. striatum, although O3 tended to induce an increase in the stomatal conductance of both species, especially T. striatum, the most sensitive species. O3 and N soil availability reduced the emission of terpenes in O. compressus and T. striatum. If these responses are confirmed as a general pattern, O3 could affect the competitiveness of these species.
Keywords: Annual pastures; BVOCS; Emissions; Gas exchange; legumes; Nitrogen deposition; Ozone; terpenes